A study to evaluate the effectiveness of an educational program on Confusion Assessment Method (CAM-ICU) in enhancing ICU delirium knowledge and skills among ICU nurses in selected hospital of Gurugram, Haryana - Ms. Aarati Chapagain; Dr. Sarika Yadav (The Bioscan, 2025)
Delirium is a major barrier to the care of patients admitted in the intensive care units globally. The Society of Critical Care Medicine recommends regular delirium monitoring among patients admitted in ICU. Methods: One group Pre-test Post-test Research design was adopted in this study. The study was conducted in 100 ICU nurses were selected by using purposive sampling technique. The data was analysed for frequency, percentage, mean, standard deviation. The effectiveness of training was analysed by pair-test. Association between pre-test level knowledge and demographic variables was analysed by using Fisher’s Exact test. Conclusion: The findings indicate a significant improvement in post-test knowledge and skills scores compared to pre-test scores and the increase was statically significant at p<0.05. There is no statistically significant association between post-test knowledge scores and any of the demographic variables (p > 0.05). The study findings suggests that educational program in a regular period will help in gaining knowledge & improving skills regarding ICU delirium among ICU nurses. Keywords Effectiveness, ICU Nurses, Educational Intervention.